Use of evidence during the COVID-19 pandemic in Peru: Contributions from the National Institute of Health - Huaman Sanchez, Karen Viviana (2022)
The COVID-19 pandemics required the countries to take decisions rapidly. Consequently, the National Institute of Health (INS) developed a series of documents of scientific evidence synthesis according to the Ministry of Health’s requirements. Based on these reports, the INS developed recommendations to update normative documents related to COVID-19’s management. This article describes the construction of a new methodology applied by the INS to synthesize scientific evidence during the COVID-19 pandemic. Moreover, it emphasizes the efforts and strategies used to guarantee the methodological quality and the implementation of the GRADE approach. Finally, it provides a short reflection on the limitations and challenges of using evidence to design national public policies in the future.